2016
DOI: 10.1096/fj.201600537r
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation impairs remyelination in mice through modulation of IL‐6

Abstract: Recent studies have revealed that social experience affects myelination. These findings have important implications for disorders that feature abnormal myelination, such as multiple sclerosis (MS), as previous studies have shown that psychosocial stress exacerbates the pathobiology of MS. However, most studies have focused on psychosocial stress during the demyelination phase of MS and have not investigated the effects of social experience on remyelination. Thus, the current study sought to determine whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
1
22
1
Order By: Relevance
“…Because BTBR mice are generally considered genetic models of ASD ( McFarlane et al, 2008 ), hypomyelination in mPFC could occur due to genetic mechanisms. The elevated expression of proinflammatory cytokines such as interleukin-6 in the brains of BTBR mice ( Wei et al, 2016 ) may cause hypomyelination, as shown in our previous study ( Makinodan et al, 2016 ). If so, myelin in the motor cortex of BTBR mice should also be thinner than that in the motor cortex of C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 55%
“…Because BTBR mice are generally considered genetic models of ASD ( McFarlane et al, 2008 ), hypomyelination in mPFC could occur due to genetic mechanisms. The elevated expression of proinflammatory cytokines such as interleukin-6 in the brains of BTBR mice ( Wei et al, 2016 ) may cause hypomyelination, as shown in our previous study ( Makinodan et al, 2016 ). If so, myelin in the motor cortex of BTBR mice should also be thinner than that in the motor cortex of C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 55%
“…Remyelination is a regenerative process by which myelin sheaths are restored to demyelinated axons ( Franklin and Ffrench-Constant, 2008 ). Ample evidence indicates that a reduced inflammatory burden favors remyelination ( Cantuti-Castelvetri et al, 2018 ; Karamita et al, 2017 ; Lan et al, 2018 ; Makinodan et al, 2016 ; Vela et al, 2002 ). Given that SCD1 inhibition and deficiency suppressed the inflammatory status of phagocytes after prolonged myelin incubation, we reasoned that abrogation of SCD1 activity could be a therapeutic target to promote remyelination.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest a brain region-specific effectiveness of enriched physical environment in remediating brain impairment of isolated mice, with a complete reversal of hippocampal structural impairments and cognitive dysfunctions, but without mitigation of mPFC pathological changes or associated anxiety and social interaction defects [12]. Re-socialization with other group housed conspecifics after adolescent social isolation, however, can restore the impaired social interaction and hypomyelination in the medial prefrontal cortex [20], suggesting a social component is necessary for complete restoration of typical behavioral responses following social isolation. The goal of our neighbor housing is to minimize the adverse effects a single housing environment can induce on behavior and physiological changes in the brain during adolescence and to minimize the chance for harm that can occur in group housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the structural and molecular changes in the brain associated with adolescent social isolation have identified reduced neuronal excitability in the dentate gyrus [17,18], and white matter structural changes in the prefrontal cortex [19,20]. Mice that were socially isolated two weeks after weaning displayed cognitive and behavioral dysfunction that was associated with alterations in the white matter tracts of the prefrontal cortex [19].…”
Section: Introductionmentioning
confidence: 99%